Counsellors perceptions of the phenomenon of concentration difficulties. Issue 1 (26th January 2021) - Hvidsten, Bente Borthne; Valle, Anne Marit
Abstract : Pupils' lack of concentration is a concern in everyday classrooms in Norway as in many other countries. Whereas research has defined different behaviour issues in classroom contexts, there has been less focus on how the counsellors, working at the Educational and Psychological Counselling Service (EPCS), describe different behaviour issues. This article is based on a study that aims to develop a deeper understanding of how the counsellors perceive the term 'concentration difficulties'. Even though the term is widely used in templates and in national strategic documents to describe pupils' disruptive behaviour, few other studies emphasise this perspective. The study has a phenomenological‐hermeneutic inspired approach and is based on individual in‐depth interviews with counsellors working at the EPCS. The key findings suggest that the counsellors understanding of the term are influenced by their personal perceptions of the term, their education and the way they facilitate adapted learning.